The history of University Midwifery Training in Krakow in the years 1780-1918 in the context of historical and organisational conditions - Dziedzic, Małgorzata; Sibiga, Elżbieta; Dziubak, Małgorzata; Janczyk, Paula (Nursing Problems / Problemy Pielęgniarstwa, 2020)
Midwifery training in Krakow started within the University structures and was closely related to the reform of the Academy in 1780. Following H. Kołłątaj and Prof. A. Badurski’s ideas, the first clinical hospital was created in Krakow, where midwifery training started. Prof. R. Czer-wiakowski gave lectures for midwives and supervised the maternity clinic. The changing political relations remodelled the structure and organisation of the school authorities, which affected the working conditions of the University. Obtaining a diploma was preceded by the so-called strict exam in front of an exam board consisting of professors. The positive result of the exam then authorised the student to take an oath in front of the Dean, the secretary, and a professor of the Faculty of Medicine, which, as stated on the diploma, gave “the right to prac-tice midwifery”. Following professors and heads of the maternity clinic made special efforts in organising midwifery courses and improving continuously difficult learning conditions. Many documents issued to midwives or provided by midwifery students have survived from their professional activity. Prof. H. Jordan achieved outstanding results in this respect, as he managed to obtain permission from the partitioning authorities to organise an independent midwifery school. It opened in 1895, and Prof. A. Mars became its head. The importance of achieving this idea promoted by Prof. H. Jordan for the further development of midwives in Krakow is worth emphasising. The independent institution took the name of the Imperial Royal School of Midwives.